2012
DOI: 10.1111/j.1471-4159.2012.07840.x
|View full text |Cite
|
Sign up to set email alerts
|

STIM1 is necessary for store‐operated calcium entry in turning growth cones

Abstract: J. Neurochem. (2012) 122, 1155–1166. Abstract Coordinated calcium signalling is vital for neuronal growth cone function and axon pathfinding. Although store‐operated calcium entry (SOCE) has been suggested to be an important source of calcium in growth cone navigation, the mechanisms that regulate calcium signalling, particularly the regulation of internal calcium stores within growth cones, are yet to be fully determined. Stromal Interaction Molecule 1 (STIM1) is a calcium‐sensing protein localized in the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 57 publications
10
58
1
Order By: Relevance
“…Similar elevation of intracellular calcium levels in response to Sema3A treatment was recently reported by Mitchell et al (2012) [51]. We also showed that increase of [Ca 2+ ] i in response to Sema3A is a concentration dependent process, and thus can be important in understanding how axonal growth cones behave in Sema3A concentration gradient.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar elevation of intracellular calcium levels in response to Sema3A treatment was recently reported by Mitchell et al (2012) [51]. We also showed that increase of [Ca 2+ ] i in response to Sema3A is a concentration dependent process, and thus can be important in understanding how axonal growth cones behave in Sema3A concentration gradient.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that modification of SERCA activity had no effect on Sema3A induced collapse rate, excluding the refilling of the reticular Ca 2+ store as significant for Sema3A induced growth cone collapse in E15 DRG neurons. Thapsigargin was however recently shown to activate ORAI channels in DRG neurons [51]. In our case such an activation of ORAI with thapsigargin had no effect on Sema3A induced elevation of [Ca 2+ ] i .…”
Section: Discussioncontrasting
confidence: 47%
“…Many different mechanisms for intracellular Ca 2+ elevation have been discovered, including release from ER stores (CICR and IICR) and entry from extracellular sources (CRAC, SOCE, and voltage-sensitive Ca 2+ channels) [22,33,34,38]. A complex pathway which interprets these intracellular Review Trends in Neurosciences August 2014, Vol.…”
Section: Discussionmentioning
confidence: 99%
“…When ER stores are depleted, the ER-resident stromal interaction molecule 1 (STIM1) localizes to the ER and plasma membrane junctions [31][32][33]. From here, STIM1 facilitates SOCE [34] through store-operated calcium (SOC) channels which utilize transient receptor potential cation (TRPC) channels and ORAI1, and calcium release-activated calcium (CRAC) channels which depend primarily on ORAI1 [33,[35][36][37]. Importantly, STIM1 localization in response to gradients of guidance cues is biased towards the up-gradient side of the growth cone, facilitating propagation of asymmetric Ca 2+ elevations [33].…”
Section: Glossarymentioning
confidence: 99%
“…Many genes that were changed in NPCs expressing HDAC2 C262A/C274A were also regulated by NO signaling, including Pdgfc (1.9-fold down-regulated) (32). Interestingly, Stim1 (2.4-fold down-regulated), an endoplasmic reticulum Ca 2+ sensor that influences neuronal development and growth cone turning, also regulates NO synthesis (33,34). Genes involved in transcriptional regulation and chromatin modification, such as Brm, the ATPase subunit of the ATP-dependent chromatin-remodeling complex BAF, were also significantly inhibited (1.8-fold) in NPCs expressing HDAC2 C262A/C274A compared with HDAC2 WT .…”
Section: Discussionmentioning
confidence: 99%